Transcriptome Profiling Reveals Indoxyl Sulfate Should Be Culpable of Impaired T Cell Function in Chronic Kidney Disease - Xiang, Fangfang; Cao, Xuesen; Shen, Bo; Chen, Xiaohong; Guo, Man; Ding, Xiaoqiang; Zou, Jianzhou (Frontiers in Medicine, 2020)
Introduction Chronic inflammation and immune system dysfunction have been evaluated as major factors in the pathogenesis of chronic kidney disease (CKD), contributing to the high mortality rates observed in these populations. Uremic toxins seem to be the potential “missing link”. Indoxyl sulfate (IS) is one of the protein-bound renal toxins. It participates in multiple pathologies of CKD complications, yet its effect on immune cell has not been studied. This study aimed to explore the genome‐wide expression profile in human peripheral blood T cells under stimulation by IS. Methods In this study, we employed RNA-sequencing transcriptome profiling to identify differentially expressed genes (DEGs) responding to IS stimulation in human peripheral T cells in vitro. Flow cytometry and western blot were used to verify the discovery in RNA-sequencing analysis. Results Our results yielded a total of 5129 DEGs that were at least twofold up-regulated or down-regulated significantly by IS stimulation and half of them were concentration-specific. Analysis of T cell functional markers revealed a quite different transcription profile under various IS concentration. Transcription factors analysis showed the similar pattern. Aryl hydrocarbon receptor (AhR) target genes CYP1A1, CYP1B1, NQO1 and AhRR were up-regulated by IS stimulation. Pro-inflammatory genes TNF-α and IFN-γ were up-regulated as verified by flow cytometry analysis. DNA damage was induced by IS stimulation as confirmed by elevated protein level of p-ATM, p-ATR, p-BRCA1 and p-p53 in T cells. Conclusion The toxicity of IS to T cells could be an important source of chronic inflammation in CKD patients. As an endogenous ligand of AhR, IS may influence multiple biological functions of T cells including inflammatory response and cell cycle regulation. Further researches are required to promulgate the underling mechanism and explore effective method of reserving T cell function in CKD.